THE INFLUENCE OF ACCOUNTABILITY AND TRANSPARENCY OF FINANCIAL MANAGEMENT OF VILLAGE FUNDS ON VILLAGE GOVERNMENT PERFORMANCE IN KOTARIH BARU VILLAGE KOTARIH DISTRICT SERGAI REGENCY - Suriana, Suriana (RADJA PUBLIKA, 2021)
This study aims to determine whether accountability and transparency in the financial management of village funds, either partially or simultaneously, have a significant effect on the performance of village government in Kotarih Baru Village, Kotarih District, Sergai Regency and how big the effect is. The method used in this study is a quantitative method with several tests, namely reliability analysis, classical assumption deviation test and linear regression. Based on the results of the primary data regression which was processed using SPSS 20, the following multiple linear regression equation was obtained: Y =6.578 +0.415 X1 + 0.438 X2.Partially, the accountability variable (X1) has a significant effect on the performance of village government in Kotarih Baru Village, Kotarih District, Sergai Regency. This means that the hypothesis in this study is accepted, as evidenced by the value of t count > t table (2,143 > 2,037). While the variable of financial management transparency of village funds (X2) has a significant influence on the performance of village government in Kotarih Baru Village, Kotarih District, Sergai Regency. This means that the hypothesis in this study is accepted, as evidenced by the value of t count > t table (2.173> 2,037). Simultaneously, the accountability variable (X1) and the transparency of village fund financial management (X2) have a significant influence on the performance of village government in Kotarih Baru Village, Kotarih District, Sergai Regency. This means that the hypothesis in this study is accepted, as evidenced by the calculated F value > F table (18,489 > 3.29). The accountability variable (X1) and the transparency of village fund financial management (X2) are able to contribute to the influence of the village government performance variable by 53.6% while the remaining 46.4% is influenced by other variables not examined in this study.